The effect of oxidation on the structure and hardness of (Zr, Hf)N coatings - Atar, Erdem; Kayali, Eyup Sabri; Cimenoglu, Huseyin (Trans Tech Publications Ltd, 2010)
In the present study, the effect of oxidation on the structure and the hardness of ternary (Zr, Hf)N coatings, whose Hf content was varied between 0 and 21 wt.%, has been systematically examined. Coatings were applied on AISI D2 tool steel plates by arc physical vapor deposition (PVD). Oxidation was conducted at 400°C for times up to 12 h in air. Ternary (Zr, Hf)N coatings are found to be more susceptible towards oxidation compared to binary ZrN coating. Oxidation caused the formation of a mixed oxide layer composed of ZrO2 and HfO2. Formation of oxide layer was accompanied by a reduction in hardness. Hardness values of Hf free and Hf alloyed (Zr, Hf)N coatings were very close to each other both in as-deposited and oxidized states. © (2010) Trans Tech Publications. © 2018 Elsevier B.V., All rights reserved.
Keywords: Coating; Hafnium; Hardness; Oxidation; PVD; ZrN